Enhancing Emotional Regulation in Children with Autism Through Theory of Mind - Badrul Hisam , Nurul Ain; Low, Hui Min (Jurnal Pendidikan Bitara UPSI, 2024)
This review paper explores the impact of Theory of Mind (ToM) on emotional regulation in children with autism spectrum disorder (ASD). This literature review examines existing research on the interplay between Theory of Mind (ToM) and emotional regulation in children with autism spectrum disorder (ASD). Theory of Mind refers to the cognitive capacity to understand and predict others' mental states, a skill often deficient in individuals with ASD. This deficiency can contribute to difficulties in social interactions and emotional regulation. The review synthesizes findings from various studies by using Scopus AI that investigate the role of ToM in emotional processing and regulation among children with autism. It explores how impaired ToM impacts the recognition, understanding, and management of emotions in this population. Additionally, the review highlights interventions aimed at enhancing ToM and their subsequent effects on emotional regulation. The synthesis of these studies reveals that targeted ToM interventions can lead to significant improvements in emotional regulation, suggesting a critical link between cognitive understanding of others' perspectives and the ability to manage one's own emotions. The paper concludes that a comprehensive understanding of the interplay between ToM and emotion regulation is crucial for developing effective interventions for children with ASD. By targeting both deficits simultaneously, interventions can be designed to address the unique needs of children with ASD, promoting better emotional regulation and social interactions.